Protective effect of Chuquiraga spinosa lessing associated with simvastatin on N-Nitroso-N-methylurea (NMU)-induced prostate cancer in rats - Arroyo-Acevedo, J.L. (2019)
Chuquiraga spinosa Lessing (ChS) has shown protective effect on N-Nitroso-N-methylurea (NMU)-induced prostate cancer in rats. Currently, statins are being studied for their pro-apoptotic and antimetastatic effects. The main objective of this research was to determine the protective effect associated with the oral administration of simvastatin and ethanolic extract of the aerial parts of ChS in the prevention of prostate cancer.